ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA PADA MATERI MATRIKS DITINJAU DARI SELF-EFFICACY - Apriliya; Mochamad Abdul Basir (Jurnal Pemikiran dan Penelitian Pendidikan Matematika (JP3M), 2019)
This research is to find out and analyze the mathematical creative thinking ability of class XI students in MA N 1 Semarang on matrix material in terms of self-efficacy. The research method used is descriptive qualitative. The instrument used was a test instrument on the matrix material with a total of 4 description items and a non-test instrument in the form of a self-efficacy questionnaire with 20 statements. The research sample was 33 students of class XI in MA N 1 Semarang City. The results of this study are that there is a relationship between self-efficacy and students creative thinking abilities on the Matrix material. Judging from the percentage of achievement based on the level of self-efficacy, if self-efficacy is high then the ability to think creatively is also high. Achievement of the percentage of indicators of creative thinking ability according to the level of self-efficacy in a row from high, medium, low, namely fluency, flexibility, elaboration, elaboration. Overall, the achievement of the ability to think creatively gets a percentage of 66.56%.